Kaempferol Inhibits Hepatic Stellate Cell Activation by Regulating miR-26b-5p/Jag1 Axis and Notch Pathway - Guangyao Zhou; Chunxue Li; Rongrong Zhang; Yating Zhan; Lifan Lin; Zhichao Lang; Qiqi Tao; Jianjian Zheng (Frontiers in Pharmacology, 2022)
Kaempferol, a natural flavonoid molecule, has demonstrated anti-inflammatory, antimicrobial and antioxidant activities. Recent studies have shown the beneficial effects of kaempferol on liver fibrosis. Notch pathway has been reported to be involved in the aberrant activation of hepatic stellate cells (HSCs). However, whether Notch pathway plays a key role in the anti-fibrotic effects of kaempferol is largely unknown. In this study, kaempferol significantly suppressed liver fibrosis in CCl4 mice, with reduced collagen deposition as well as restored liver function. In vitro, kaempferol enhanced the suppression of HSC activation, with a decrease in α-SMA as well as collagen level. It was found that Notch pathway played an important role in kaempferol-reduced the activation of HSCs. Jag1, a ligand of Notch pathway, was obviously inhibited by kaempferol. Overexpression of Jag1 effectively abolished kaempferol-induced HSC inactivation. Furthermore, Jag1 was demonstrated as a target of microRNA-26b-5p (miR-26b-5p). Interestingly, miR-26b-5p inhibitor prevented HSC activation inhibition caused by kaempferol. Further studies indicated that kaempferol inhibited Notch pathway via miR-26b-5p and Jag1, leading to HSC inactivation. Collectively, we demonstrate that kaempferol could inhibit HSC activation, at least in part, via miR-26b-5p-mediated Jag1 axis and Notch pathway. Kaempferol may serve as a promising drug in the application of treating liver fibrosis.